2005
DOI: 10.1038/sj.bjc.6602724
|View full text |Cite
|
Sign up to set email alerts
|

Salvage high-dose chemotherapy for children with extragonadal germ-cell tumours

Abstract: We reviewed the European Group for Blood and Marrow Transplantation (EBMT) experience with salvage high-dose chemotherapy (HDC) in paediatric patients with extragonadal germ-cell tumour (GCT). A total of 23 children with extragonadal GCT, median age 12 years (range 1 -20), were treated with salvage HDC with haematopoietic progenitor cell support. The GCT primary location was intracranial site in nine cases, sacrococcyx in eight, retroperitoneum in four, and mediastinum in two. In all, 22 patients had a nongerm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 20 publications
0
48
0
2
Order By: Relevance
“…Chemotherapy regimens may include such agents as cisplatin-etoposideifosfamide, cisplatin-etoposide and etoposidecarboplatin. High-dose chemotherapy with autologous stem cell rescue conditioned with carboplatin and etoposide or etoposide and thiotepa can be used in patients who relapsed followed by RT [24]. Time to relapse can vary.…”
Section: Current Managementmentioning
confidence: 98%
“…Chemotherapy regimens may include such agents as cisplatin-etoposideifosfamide, cisplatin-etoposide and etoposidecarboplatin. High-dose chemotherapy with autologous stem cell rescue conditioned with carboplatin and etoposide or etoposide and thiotepa can be used in patients who relapsed followed by RT [24]. Time to relapse can vary.…”
Section: Current Managementmentioning
confidence: 98%
“…Most studies of pediatric GCTs include both neonates and older children, making it difficult to discern the precise pathology and clinical course of extragonadal GCTs in the older child. [2][3][4][5][6] A recent study has suggested that age Z12 years is a significantly adverse prognostic factor, especially for thoracic tumors, and therefore may represent the transition point to adult type tumors. 7 In addition to prognostic differences, it is well documented that pediatric GCTs are distinct from adult GCTs cytogenetically.…”
Section: Pediatric Extragonadal Gctsmentioning
confidence: 99%
“…kleinere unkontrollierte Pilotstudien, in denen ebenfalls über langfristige Heilungserfolge in mehr als 50% der Fälle berichtet wird [1,13] [5,8,16,25]. Bei Tumorrezidiven finden Hochdosis-Chemotherapien Verwendung, wobei deren Stellenwert als Erstlinientherapie jedoch noch unklar ist [6].…”
Section: Long-term Follow-up Of Patients With Suprasellar Germinomasunclassified